Coupling a ladder to the safety net: reinventing MGNREGA for asset creation. Issue 4 (19th May 2019) - Tambe, Sandeep; Bhutia, Nima Tashi; Pradhan, Sarika; Basi, Jigme
ABSTRACT: India's rural employment act (MGNREGA), the world's largest public works programme, is designed to guarantee wage employment as a statutory right. It is viewed by many as a drain on the public exchequer, as wages are paid but durable assets are not created. Can this safety net be restructured to double up as a ladder of opportunity for the poor without altering its entitlement-based framework? This article shows that implementing four sets of interventions – policy for household livelihood assets, convergence approaches, pro-poor participatory planning, and strengthening accountability, can accelerate the creation of livelihood assets in the lands of the poor.